DISPARITAS KEWENANGAN PENGAJUAN PERMOHONAN KEPAILITAN DAN PKPU PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2025 TENTANG BUMN STUDI KRITIS TERHADAP KEDUDUKAN DANANTARA DAN PASAL 2 AYAT (5) UNDANG-UNDANG KEPAILITAN DAN PKPU - Saputra, Doni Romdoni; Wulandari, Fenny (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study is entitled “Disparities in the Authority to File for Bankruptcy and PKPU after the Enactment of Law Number 1 of 2025 concerning State-Owned Enterprises: A Critical Study of the Position and Article 2 Paragraph (5) of the Bankruptcy and PKPU Law”. This study was motivated by the strengthening of the state's role in the management of State-Owned Enterprises (SOEs) after the enactment of the 2025 SOE Law, which allows the state to have greater control over the financial management and debt restructuring of SOEs. The research method used is normative legal research, with a statute approach, case approach, and conceptual approach. Data collection techniques were carried out through library research with primary legal materials in the form of the 2025 SOE Law, Law No. 37 of 2004 concerning Bankruptcy and PKPU, as well as related court decisions; secondary legal materials in the form of books, scientific journals, academic articles, and previous research. The analysis was conducted using a prescriptive-analytical qualitative approach to assess legal norms and legal policy implications in depth. The results of the study show that after the 2025 SOE Law, there is a significant disparity in authority between SOEs and private creditors, whereby the filing of bankruptcy and PKPU petitions has become more dependent on state approval. This creates legal uncertainty for creditors, potential moral hazard incentives for SOE managers, and the risk of undermining the principles of equality before the law and fair business competition. In terms of legal politics, state dominance can lead to a shift in interests from private rights to national stability, which requires transparent mechanisms and clear legal procedures. The conclusion of this study emphasizes that the legal treatment of SOEs must be proportional, maintaining a balance between public interests and private creditor rights, and minimizing legal and market distortions. This study presents a new perspective on the long-term implications of the 2025 SOE Law on the bankruptcy and PKPU systems, which is an important contribution to Indonesian economic law literature.